Invariant Object Recognition Using Radon-based Transform - Arodź, Tomasz (Computing and Informatics, 2012)
The properties of the Radon transform are used to derive the transformation invariant to translation, rotation and scaling. The invariant transformation involves translation compensation, angle representation and 1-D Fourier transform. The new object recognition method is studied experimentally in two domains, mammogram labels recognition and face recognition. For mammogram labels, the recognition accuracy is 97 %, while in case of faces it reaches 96 %.